INCULTURATION EXPERIMENTAL THEOLOGY AMONG THE TOBA-BATAKS OF NORTH SUMATRA Incarnation-Pascal Approach - Sinaga, Anicetus B (LOGOS, 2009)
A map setting and identification of the Toba-Batak in North Sumatra would be appropriate before dealing with the theme of inculturation among the Toba-Batak. In addition a short treatise on their inculturation experience, after an overwhelming conversion to Christianity since 19th century would be well to have a logic of inculturation exposition. It is not only experience, but most of all we desire a theological foundation, as it is exposed in the Vatican Council II, especially in the document Ad Gentes.